Didactic narrative strategies at A1/A2 level. Linguistic and cultural education within the framework of the “Polish language beyond borders” project - Rzeszutko, Małgorzata; Gabryś-Sławińska , Monika (Papers in Linguistics, 2025)
The aim of the article is to present didactic narrative strategies applied at the A1/A2 level in a group of adults of Polish origin living in Brazil (a case study). The beneficiaries of the “Polish language beyond borders” project learnt the Polish language and culture in an integrated way with the use of the series of educational videos entitled Lublin snapshots and educational packages accompanying them. Learning a language through the presentation of culture and contact with it produces the most optimal results. This type of didactic approach is in line with Content and Language Integrated Learning (CLIL Education), which offers a student’s overall development involving sociological, intellectual and emotional aspects. The applied didactic narrative strategies such as: SATISFACTION, DIALOGUE, CHALLENGE and MULTICULTURALISM created an opportunity for the learners to form independent utterances based on authentic communicative situations. The educational task was to shape and develop both receptive and productive skills, with emphasis on listening, speaking and reading practice. The implementation of the four didactic narrative strategies facilitated an interesting way of transferring linguistic and cultural knowledge, properly motivating students, enhancing their linguistic and cultural creativity as well as guiding them in getting acquainted with cultural realities. All this made it possible to create A SATISFACTORY DIALOGUE in the context of the CHALLENGES OF MULTICULTURALISM.